Predictors of in-hospital mortality following mitral or double valve replacement for rheumatic heart disease - Sharma, Apurb; Panthee, Nirmal; Bajracharya, Smriti Mahaju; Rajbanshi, Bijoy Gopal; Koirala, Raamesh Raj; Sharma, Jyotindra; Pokharel, Jeju Nath (Nepalese Heart Journal, 2016)
Backgrounds and Aims: Factors affecting outcome of mitral valve replacement in rheumatic population of Nepal is unknown. The aim of this study was to identify the predictors of in-hospital mortality in patients undergoing mitral or double valve replacement in Nepal.Methods: A retrospective observational study was designed to evaluate the outcome of patients who underwent mitral valve replacement with or without concomitant other valvular surgery during a period of one year in a tertiary care cardiac centre in Nepal. Data were analysed to find the significant predictors of in-hospital mortality.Results: A total of 411 patients fulfilled the inclusion criteria. The overall in-hospital mortality was 4.1% (95% CI 2.18-6.02). A cutoff value for higher mortality obtained using ROC curve for age was 37.5 years; and for duration of mechanical ventilation was 8.5 hours. Multivariate logistic regression model identified increasing age (>37.5 years), OR 2.05 (95% CI 0.77-5.45), p=0.001; NYHA Class III and IV, OR 15.18 (95%CI 0.9-54.53), p20, OR 9.90 (95% CI 3.48-28.15), p8.5 hours, OR 22.96 (95% CI 5.15-52.10), p 2 days, OR 1.31 (95% CI 0.49-3.46), p